Buddhism and Political Behaviour - Kandel, Ishwori Prasad (Historical Journal, 2020)
The Buddha lived and taught 2.500 years before the field of psychology was established, but the teaching he left behind introduce wide-ranging and profound analysis of human behaviour that overlap. Buddhist Festivals are always joyful occasions. The most significant celebration takes place every May on the night of the full moon, when Buddhists all over the world celebrate the birth, enlightenment and death of the Buddha over 2,500 years ago. It has come to be known as Buddha Day. Buddhism, in its natural form, is not a religion; rather it is a tradition that focuses on personal spiritual development. The Buddha intended his philosophy to be a practical one, aimed at the happiness of all creatures. While he outlined his metaphysics, he did not expect anyone to accept this on faith but rather to verify the insights for themselves; his emphasis was always on seeing clearly and understanding. To achieve this, however, requires a disciplined life and a clear commitment to liberation; the Buddha laid out a clear path to the goal and also observations on how to live life wisely. The core of this teaching is contained in the Noble Eightfold Path, which covers the three essential areas of Buddhist practice: ethical conduct, mental discipline and wisdom. The goals are to cultivate both wisdom and compassion; then these qualities together will enable one ultimately to attain enlightenment.